Ayaq World SDN BHD MSMe Business Development Malaysia with the Implementation of Digital Marketing Strategies - Setiadi, Iwan Kresna; Supriadi, Yudi Nur; Winarto, Edy; Putra, Andri Muharizal; Aliyudin, Muhammad; Huridi, Muhammad Hanafia; Kusuma, Jaka Wijaya (International Journal of Engagement and Empowerment (IJE2), 2024)
The Community Service International (CSI) project is a collaboration between the Veteran National Development University of Jakarta, Indonesia, and the University of Kuala Lumpur, Malaysia, which focuses on improving the sales performance of Micro, Small, and Medium Enterprises (MSMEs). This activity targets Ayaq World Sdn Bhd (AWSB), a small business under the guidance of Majlis Amanah Rakyat (MARA) in Kuala Lumpur, which is engaged in the production and marketing of natural fruit juices.  The CSI team visited production sites, held face-to-face discussions, and analyzed the conditions and challenges faced by AWSB. Based on this analysis, the team proposed solutions, including the use of digital marketing to expand the market, increase interaction with consumers, and build brand awareness. This is expected to significantly increase AWSB's sales turnover. In addition to providing practical solutions, this activity also shows how academic collaboration can strengthen the relationship between the world of education and industry, create sustainable synergies, and encourage innovation in business strategies. Thus, CSI has succeeded in creating a sustainable positive impact, not only for AWSB, but also for other MSMEs who can benefit from the results and findings of this activity